The Strata Diana Patricia Jaramillo (London Journal of Research In Humanities and Social Sciences, 2023)
The strata by Juan Cárdenas is a transdisciplinary work that exceeds the meaning of a short novel; although in principle it starts from the need of a man to reconstruct some images of his childhood that he believes are the reason for his despondency; for his not being in the world, for his illness; in reality this event is just an excuse to go through a series of subsidiary stories that confront him with a profound reality: to recognize himself as a man who is dead but has not realized it, and with an imperious need: to heal. During the process, he must confront his own buzzing; that which is an eternal presence, and that of those who are part of his environment, through the action of multiple voices that participate in the same search, from different insights, social spaces, and geographical spaces. All of this is an exercise of thought that not only makes literature, and experiments with language but is also interested in Latin America, in its individual and collective memories, in the people who are not afraid of death because they have always been dead.
Keywords: strata; illness; buzzing; childhood; jungle; insomnia; ghosts; cane field; black people; pacific coast